PEMBERIAN ISOTONIC QUADRICEPS EXERCISE LEBIH EFEKTIF DALAM MENINGKATKAN MOBILITAS LANSIA DARIPADA ISOMETRIC QUADRICEPS EXERCISE DI DESA PITRA, KECAMATAN PENEBEL, TABANAN - Putu Aditya Mahardika; Ni Wayan Tianing; I Gusti Ayu Artini; Ari Wibawa (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2016)
ABSTRACTDecreased muscle strength lead to a decline in mobility to the elderly. The purpose of this study to prove that the administration of isotonic quadriceps exercise is more effective in increasing the mobility of the elderly than isometric quadriceps exercise. Experimental research with pre-test and post-test two group design. The mean decrease in group 1 time of 3.79 seconds with p = 0.000 (p <0.05), group 2 occurs an average decrease in time by 2.14 seconds with p = 0.000 (p <0.05). This means that in every group increased mobility significantly. Different test the difference between group 1 and group 2 showed no significant difference with the result p = 0.002 (p <0.05). Based on the results of that study concluded that application of isotonic quadriceps exercise is more effective in increasing the mobility of the elderly than isometric quadriceps exercise. Keywords: Mobility, quadriceps femoris muscle, isotonic quadriceps exercise, isometric quadriceps exercise.